Double Desire: Transculturation and Indigenous Contemporary Art - McLean, Ian (Cambridge Scholars Publishing, 2014)
ouble Desire challenges the tendency by critics to perpetuate an aesthetic apartheid between Indigenous and Western art. The double desire explored in this book is that of the divided but also amplified attractions that occur between cultural traditions in places where both indigenous and colonial legacies are strong. The result, it is argued, produces imaginative transcultural practices that resist the assimilation or acculturation of Indigenous perspectives into the dominant Western...
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé